Human nature and transhumanism - Postigo Solana, Elena (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
So far we have collected some of the characteristic notes of human nature: its intelligence, its social, historical, biographical and cultural dimension. Other traits common to all human beings could be pointed out, such as freedom, dignity, finitude and vulnerability. We did not pretend to be exhaustive but to point out a third way in the understanding of human nature (between biologicism and socioculturalism). A third way is possible, which collects some elements from classical thought to our days, passing through contemporary authors such as Zubiri, personalists and others, and making a proposal of human nature as that which makes the human being who he is and not just any other animal. The specificity of the human is undeniable, and its irreducibility to matter remains on the horizon as a vanishing point, where perhaps it is necessary to invoke the dimension of the enigma or the mystery, in the words of Professor Miguel García-Baró, and recover the verticality of the being human, the ultimate horizon of understanding about who he is, his meaning and significance. «Science is cumulative, wisdom is not», said Jérôme Lejeune. Science progresses exponentially, at an accelerated speed, transhumanism is proof of this; on the contrary, wisdom does not. The development of the technical-instrumental reason is being very fast and accelerated; Wisdom reason, on the other hand, proceeds slowly, without the ability to analyze in calm and detail all that these changes imply. Greater reflection is required of us about who we are and where we are going as a species. Transhumanism and posthumanism raise the question of utility, but not those of meaning and the ultimate, or first, meaning of human existence.